Language Theory, Phonology and Etymology in Buddhism and their relationship to Brahmanism - Levman, Bryan Geoffrey (Buddhist Studies Review, 2017)
The Buddha considered names of things and people to be arbitrary designations, with their meaning created by agreement. The early suttas show clearly that inter alia, names, perceptions, feelings, thinking, conceptions and mental proliferations were all conditioned dhammas which, when their nature is misunderstood, led to the creation of a sense of ‘I’, as well as craving, clinging and afflictions. Although names were potentially afflictive and ‘had everything under their power’ (Nama Sutta), this did not mean that they were to be ignored or even neglected; words were to be penetrated and thoroughly understood, as an essential instrument for liberation. One of the problems of transmitting the Buddha’s teachings was the large number of disciples who did not speak an Indo-Aryan language as their first language or spoke a dialect different from that of the Teacher. This also led to altered transmission of the Vinaya and Suttas by disciples who could not hear certain phonological distinctions not present in their own language or dialect. Hundreds of these anomalies are preserved in the different editions of the canon, testifying to these transmission ambiguities. The passages dealing with this problem provide a valuable insight into the phonological issues that the early sangha had to deal with to try and preserve the integrity of the sasana. At the same time the etymological practices of Brahmanism were imported into Buddhism very early, probably from the time of the Buddha himself, to demonstrate the intellectual superiority of the Buddha and his teachings. Despite the Buddha’s teachings on the arbitrary nature of language, the commentarial and grammatical traditions developed a sophisticated theoretical framework to analyse, explicate and reinforce some of the key Buddhist doctrinal terms. Also, an elaborate classification system of different types of names (naman) was developed, to show that the language of the Buddha was firmly grounded in saccikattha, the highest truth, and that some terms were spontaneously arisen (opapatika), even though such a concept — that words by themselves could arise spontaneously and directly embody ultimate truth — was quite foreign to their Founder.